Apakah Inovasi Lingkungan Perusahaan dan Profitabilitas Mempengaruhi Risiko Jatuhnya Harga Saham - Silva Izza Majida; Suwarno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the effect of environmental innovation and profitability on the risk of stock price drops in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Using quantitative methods, the research examines annual financial reports for 2021-2022. The findings reveal that both environmental innovation and profitability significantly impact stock price risk. Companies that implement effective environmental innovation strategies reduce long-term risks and enhance investor confidence, while high profitability strengthens financial performance and lowers volatility. These results provide critical insights for investors and managers to mitigate financial risks.